The Effectiveness of the Utilization of Epic Pen in Mathematics Education Course 2 - Putri Milanda Bainamus; Asti Putri Kartiwi; Syaipul Amri; Edy Susanto; Pamela Mikaresti; Bogy Restu Ilahi; Meri Andaria; Mesterjon; Adi Asmara (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This study aims to describe the effectiveness of the use of epic pens in mathematics education 2 courses. The method of this research is quantitative descriptive. The subjects of this study are 26 students of the Elementary Education Study Program (PGSD) Semester five of the Open University. The instrument used was 8 questions. The results of the study obtained an average score on a scale of five, which was 4.37. These results when consulted with the Weighted Means Score (WMS) table in the range of 4.01 - 5.00 indicate a very effective category. So it can be concluded that the epic pen is very effective in the mathematics education course 2 PGSD semester five of the Open University. Keywords: Effectiveness, Epic Pen, Mathematics, Education. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan efektivitas pemanfaatan epic pen pada mata kuliah pendidikan matematika 2. Metode penelitian ini adalah deskriftif kuantitatif. Subjek penelitian ini adalah 26 mahasiswa Program Studi Pendidikan Dasar (PGSD) Semester lima Universitar Terbuka. Instrumen yang digunakan yaitu 8 pertanyaan. Hasil penelitian perolehan skor rata-rata pada skala lima yaitu 4,37. Hasil tersebut jika dikonsultasikan dengan tabel Weighted Means Score (WMS) pada rentang 4,01 - 5,00 menunjukkan kategori sangat efektif. Maka dapat disimpulkan bahwa epic pen sangat efektif digunakan pada mata kuliah pendidikan matematika 2 PGSD semester lima Universitas Terbuka. Kata Kunci: Efektivitas, Epic Pen, Matematika, Pendidikan.